The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-02204-3
|View full text |Cite
|
Sign up to set email alerts
|

Prescription pattern analysis for antibiotics in working-age workers diagnosed with common cold

Abstract: Antimicrobial resistance is a major health concern. A primary cause is the inappropriate use of antimicrobials, particularly by patients with upper respiratory tract infection. However, baseline information for antibiotic use for common cold before being applied the National Action Plan on Antimicrobial Resistance in Japan is lacking. Here, we analyzed the inappropriate use of antibiotics in the working-age workers. We used large claims data from an annual health check-up for at least 5 consecutive years. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…The increase in medication prescriptions is potentially associated with an increase in healthcare associated costs as well medication associated adverse events. Comparing with existing literature: Our 16% antibiotics prescription rates in NP compare favorably with the 51% prescription rate in the United States albeit in an old study and the 28% in a newer one, or the 49% prescription rate in a more recent study in Japan [16,17,18]. Our rate is considerably higher than the 4.6% prescription rate reported in the control group of an interventional study in Spain [19].…”
Section: Population and General Informationsupporting
confidence: 66%
“…The increase in medication prescriptions is potentially associated with an increase in healthcare associated costs as well medication associated adverse events. Comparing with existing literature: Our 16% antibiotics prescription rates in NP compare favorably with the 51% prescription rate in the United States albeit in an old study and the 28% in a newer one, or the 49% prescription rate in a more recent study in Japan [16,17,18]. Our rate is considerably higher than the 4.6% prescription rate reported in the control group of an interventional study in Spain [19].…”
Section: Population and General Informationsupporting
confidence: 66%
“…Our study resulted in a higher AMU in Western Japan than that in Eastern Japan, which was described in the previous study using data before the action plan implementation. For the AMU in general, previous studies, including a systematic review, revealed that females were more likely to receive antimicrobials compared with males [28, 29,30,31], although other studies showed that males had more antibiotic prescriptions than females [32,33]. While the impact of gender on the AMU varies by situation, further investigations regarding the factors related with gender difference in the population are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Our study resulted in a higher AMU in Western Japan than that in Eastern Japan, which was described in the previous study using data before the action plan implementation. For the AMU in general, previous studies, including a systematic review, revealed that female individuals were more likely to receive antimicrobials compared with male individuals [ 30 33 ], although other studies showed that male individuals had more antibiotic prescriptions than female individuals [ 34 , 35 ]. The study could not evaluate the impact of urinary tract infection, which was more frequently reported in female individuals compared to male individuals [ 36 ].…”
Section: Discussionmentioning
confidence: 99%